TU‐G‐204‐09: The Effects of Reduced‐ Dose Lung Cancer Screening CT On Lung Nodule Detection Using a CAD Algorithm - Young, S; Lo, P; Kim, G; Hsu, W; Hoffman, J; Brown, M; McNitt‐Gray, M (Medical physics (Lancaster), 2015)
Purpose: While Lung Cancer Screening CT is being performed at low doses, the purpose of this study was to investigate the effects of further reducing dose on the performance of a CAD nodule‐detection algorithm. Methods: We selected 50 cases from our local database of National Lung Screening Trial (NLST) patients for which we had both the image series and the raw CT data from the original scans. All scans were acquired with fixed mAs (25 for standard‐sized patients, 40 for large patients) on a 64‐slice scanner (Sensation 64, Siemens Healthcare). All images were reconstructed with 1‐mm slice thickness, B50 kernel. 10 of the cases had at least one nodule reported on the NLST reader forms. Based on a previously‐published technique, we added noise to the raw data to simulate reduced‐dose versions of each case at 50% and 25% of the original NLST dose (i.e. approximately 1.0 and 0.5 mGy CTDIvol). For each case at each dose level, the CAD detection algorithm was run and nodules greater than 4 mm in diameter were reported. These CAD results were compared to “truth”, defined as the approximate nodule centroids from the NLST reports. Subject‐level mean sensitivities and false‐positive rates were calculated for each dose level. Results: The mean sensitivities of the CAD algorithm were 35% at the original dose, 20% at 50% dose, and 42.5% at 25% dose. The false‐positive rates, in decreasing‐dose order, were 3.7, 2.9, and 10 per case. In certain cases, particularly in larger patients, there were severe photon‐starvation artifacts, especially in the apical region due to the high‐attenuating shoulders. Conclusion: The detection task was challenging for the CAD algorithm at all dose levels, including the original NLST dose. However, the false‐positive rate at 25% dose approximately tripled, suggesting a loss of CAD robustness somewhere between 0.5 and 1.0 mGy. NCI grant U01 CA181156 (Quantitative Imaging Network); Tobacco Related Disease Research Project grant 22RT‐0131.